Reaction pathway to the synthesis of anatase via the chemical modification of titanium isopropoxide with acetic acid - Parra, R. [UNESP]; Goes, M. S. [UNESP]; Castro, M. S.; Longo, Elson [UNESP]; Bueno, Paulo Roberto [UNESP]; Varela, José Arana [UNESP] (Amer Chemical Soc, 2008)
Anatase nanoparticles were obtained through a modified sol-gel route from titanium isopropoxide modified with acetic acid in order to control hydrolysis and condensation reactions. The modification of Ti(O(i)Pr)(4) with acetic acid reduces the availability of groups that hydrolyze and condense easily through the formation of a stable complex whose structure was determined to be Ti(OCOCH(3))(O(i)Pr)(2) by means of FTIR and (13)C NMR. The presence of this complex was confirmed with FTIR in the early stages of the process. A doublet in 1542 and 1440 cm(-1) stands for the asymmetric and symmetric stretching vibrations of the carboxylic group coordinated to Ti as a bidentate ligand. The gap of 102 cm(-1) between these signals suggests that acetate acts preferentially as a bidentate rather than as a bridging ligand between two titanium atoms. The use of acetic acid as modifier allows the control of both the degree of condensation and oligomerization of the precursor and leads to the preferential crystallization of TiO(2) in the anatase phase. A possible reaction pathway toward the formation of anatase is proposed on the basis of the intermediate species present in a 1:1 Ti(O(i)Pr)(4):CH(3)COOH molar system in which esterification reactions that introduce H(2)O into the reaction mixture were seen to be negligible. The Rietveld refinement and TEM analysis revealed that the powder is composed of isotropic anatase nanocrystallites.